STORY TOMB OF SHEIKH IBRAHIM MUFTI IN JORONG PARAK BARU NAGARI TARAM DISTRICT HARAU REGENCY LIMAPULUH KOTA (A FOKLOR REVIEW) - Liga Febrina; Hasmi Novianti (Jurnal Ilmu Pendidikan Ahlussunnah, 2023)
This research is motivated by the existence of the story of the tomb of Sheikh Ibrahim Mufti which has strangeness and supernatural powers in the future which are always associated with his sacredness. This is what encourages people and pilgrims to visit the sacred Tomb of Sheikh Ibrahim Mufti. This study aims to reveal how the story of Syekh Ibrahim Mufti's grave in Surau Tuo Nagari Taram is. This type of research is a qualitative research with descriptive method. The research location for the story of Sheikh Ibrahim Mufti's tomb is in the Tuo Nagari Taram surau, to be precise, in Jorong Parak Baru. Researchers as the main instrument require recording equipment in the form of camcorders, recording sheets, and interview guidelines. Data collection was carried out in two stages, first the data was collected through recording, where the informant's speech was recorded using audiovisual. The results of the recording are transcribed into written form. Furthermore, the results of the transcription are transliterated from the regional language into Indonesian. The second stage, data about the story of Sheikh Ibrahim Mufti's grave was collected through three techniques, namely direct observation, interviews and documentation of the story of Sheikh Ibrahim Mufti's grave in Tuo Nagari Taram surau.